KAJIAN PENGARUH KONSENTRASI ENZIM TRIPSIN DAN PH TERHADAP KUALITAS VIRGIN COCONUT OIL - Nana Dyah Siswati; Eko Nurcahyo; Masyitoh Febrianti (BUANA SAINS, 2007)
Coconut oil is vegetable oil extracted from coconut flesh. Based on the content of its fatty acid, coconut oil is put into laurat acid oil group because it has the biggest content of laurat acid which is 53 % compared to other fatty acids. One of the methods of VCO extraction is the use of protease. The research method was performed by adding Tripsin enzyme having 0 %, 0.02 %, 0.04 %, 0.06 % and 0.08 % concentrate into coconut milk with various pH (3, 4, 5, 6, 7). Then it was stirred and left for about 20 hours. Finally, the oil was extracted and the laurat acid content was analyzed. The result showed that the best condition was obtained when Tripsin enzyme concentrate was 0.08 % and pH was 6 with the obtained laurat acid was 52.68 %